Profile of serum electrolytes in critically Ill children: A prospective study - Agarwal, Neha; Rao, Yashwant K; Saxena, Rachit; Acharya, Rupanjali (Indian Journal of Child Health, 2018)
Objective: The objective of this study is to identify the various electrolyte abnormalities in critically ill children admitted to pediatric intensive care unit (PICU) and their association with morbidity and mortality. Methods: This was a hospital-based prospective observational study conducted on 180 critically ill children in the age group 2 months to 15 years admitted in the PICU of a tertiary care hospital. Venous blood sample was obtained for the estimation of serum sodium, potassium, calcium, magnesium, and phosphate. The incidence of electrolyte abnormalities and their relation to the primary illness was calculated. Morbidity (mean duration of hospital stay) and mortality rates were evaluated and compared to patients with normal electrolyte levels. Results: Electrolyte abnormalities were seen in 108 children (60%); 72 patients (40%) were having normal electrolyte levels. Most common abnormality seen was hyponatremia in 50.5% patients (n=91). Morbidity and mortality were also higher in these patients. Overall mortality with dyselectrolytemia was 30.5% (n=33) as compared to those with normal electrolyte levels (4.1%, n=3) and was statistically significant (p<0.01). Conclusion: The present study showed a high incidence of electrolyte abnormalities in acutely ill children admitted to PICU. Since the specific symptoms of electrolyte abnormality often merge with the underlying disease, they remain unrecognized and contribute significantly to the morbidity and mortality besides the primary illness. Close monitoring and appropriate correction of electrolyte abnormalities will be useful in lowering mortality.